Reference Clock Signal Distribution for Quantum Key Distribution - Ramos, Mariana F.; Silva, Nuno A.; Muga, Nelson J.; Pinto, Armando N. (Anais do Workshop de Comunicação e Computação Quântica (WQuantum), 2021)
Quantum key distribution (QKD) requires high synchronization accuracy, specially in systems that use gated detectors at the receiver station. In this work, we present a reference clock distribution method to support long-term QKD. An average quantum bit error rate (QBER) of 1.8% was measured, which is suitable for different QKD implementations. This method is suitable for longdistance and long-term QKD implementations and does not require additional transmitted qubits for synchronization.